2023
DOI: 10.3390/su15021484
|View full text |Cite
|
Sign up to set email alerts
|

Demand Response Management of a Residential Microgrid Using Chaotic Aquila Optimization

Abstract: In this paper, Chaotic Aquila Optimization has been proposed for the solution of the demand response program of a grid-connected residential microgrid (GCRMG) system. Here, the main objective is to optimize the scheduling pattern of connected appliances of the building such that overall user cost are minimized under the dynamic price rate of electricity. The GCRMG model considered for analysis is equipped with a fuel cell, combined heat and power (CHP), and a battery storage system. It has to control and sched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The experimental result showed that incorporation of chaotic AO greatly improves the utilized neural network performance. Kujur et al [ 72 ] presented a chaotic AO in order to solve the demand response program in a residential microgrid that is connected to the main power grid. The primary goal is to reduce total user costs in a building with a variable power rate by optimizing the scheduling pattern of linked devices.…”
Section: Related Work On Classical Ao and Its Improved Variantsmentioning
confidence: 99%
“…The experimental result showed that incorporation of chaotic AO greatly improves the utilized neural network performance. Kujur et al [ 72 ] presented a chaotic AO in order to solve the demand response program in a residential microgrid that is connected to the main power grid. The primary goal is to reduce total user costs in a building with a variable power rate by optimizing the scheduling pattern of linked devices.…”
Section: Related Work On Classical Ao and Its Improved Variantsmentioning
confidence: 99%
“…To address the depletion of fossil fuels and the escalating impact of climate change [1][2][3], numerous countries are actively pursuing a low-carbon and sustainable transformation of their energy infrastructure [4,5]. Hydrogen, characterized by its status as a zero-carbon energy source boasting high-energy density, diverse production pathways, and extensive storage capabilities [6], has garnered increasing attention.…”
Section: Introductionmentioning
confidence: 99%
“…With reduced strain on the BESS, this grouping can successfully and efectively resolve the variable power variations. Terefore, an efective control approach is crucial for the HESS to operate at its best under varied load demands [10,11]. In [12], a HESS combining batteries and supercapacitors is presented using sophisticated electrothermal modelling.…”
Section: Introductionmentioning
confidence: 99%